Rapid electrochemical detection of coronavirus SARS-CoV-2 - Thanyarat Chaibun (Nature Portfolio, 2021)
Currently the most common method of COVID-19 diagnosis is by qRT-PCR which is slow and requires expensive instrumentation. Here the authors report an electrochemical biosensor based on isothermal rolling circle amplification for rapid detection of SARS-CoV-2 in clinical samples.